2016
DOI: 10.7717/peerj.2008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of scopolamine on motor control and attentional processes

Abstract: Background: Motion sickness may be caused by a sensory conflict between the visual and the vestibular systems. Scopolamine, known to be the most effective therapy to control the vegetative symptoms of motion sickness, acts on the vestibular nucleus and potentially the vestibulospinal pathway, which may affect balance and motor tasks requiring both attentional process and motor balance. The aim of this study was to explore the effect of scopolamine on motor control and attentional processes.Methods: Seven subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Similarly, Bestaven and colleagues reported no effect on reaction time in a scoring task up to 30 min after the injection of scopolamine at a dose of 0.2 mg (Bestaven et al, 2016). However, these authors reported an effect on posture and on vestibulomotor control of the lower limbs (Bestaven et al, 2016), which could be related to the effect of scopolamine on the brainstem reported in animals (Gall et al, 2007). We found slower RT in CPT and PVT, whereas only the latter reached the level of statistical significance.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, Bestaven and colleagues reported no effect on reaction time in a scoring task up to 30 min after the injection of scopolamine at a dose of 0.2 mg (Bestaven et al, 2016). However, these authors reported an effect on posture and on vestibulomotor control of the lower limbs (Bestaven et al, 2016), which could be related to the effect of scopolamine on the brainstem reported in animals (Gall et al, 2007). We found slower RT in CPT and PVT, whereas only the latter reached the level of statistical significance.…”
Section: Discussionmentioning
confidence: 96%
“…Lower doses of 0.22 mg induced only peripheral signs, but did not impair cognitive functions ( Flicker et al, 1990 ). Similarly, Bestaven and colleagues reported no effect on reaction time in a scoring task up to 30 min after the injection of scopolamine at a dose of 0.2 mg ( Bestaven et al, 2016 ). However, these authors reported an effect on posture and on vestibulomotor control of the lower limbs ( Bestaven et al, 2016 ), which could be related to the effect of scopolamine on the brainstem reported in animals ( Gall et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Tal et al ( 65 ) reported a significant decrease in cVEMP p13 latency following scopolamine administration. Bestaven et al ( 16 ) demonstrated a significant reduction of ~30% of the vestibulo-spinal reflexes following galvanic vestibular stimulation associated with a decrease in balance test and vertical perception. In cat, no direct effect of scopolamine on the VOR was found at low doses, while at high doses the effects were confounded by sedation ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, one of the most efficient drugs to prevent in particular space motion sickness ( 10 , 11 ) is scopolamine ( 12 14 ), a muscarinic antagonist commonly administered through transdermal patches. While its molecular effects are well characterized, its putative action on the peripheral and/or central vestibular system, at the neuronal ( 15 ) and behavioral levels ( 14 , 16 ) have still to be specified. Several studies have also tried non-pharmacological approaches to help prevent motion sickness by habituating the system to vestibular stimulation ( 17 20 ).…”
Section: Introductionmentioning
confidence: 99%